2016
DOI: 10.1371/journal.pone.0157119
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Inequalities in Psychological Distress among Urban Adults: The Moderating Role of Neighborhood Social Cohesion

Abstract: BackgroundVarious studies have reported socioeconomic inequalities in mental health among urban residents. This study aimed at investigating whether neighborhood social cohesion influences the associations between socio-economic factors and psychological distress.MethodsCross-sectional questionnaire study on a random sample of 18,173 residents aged 16 years and older from 211 neighborhoods in the four largest cities in the Netherlands. Psychological distress was the dependent variable (scale range 10–50). Neig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 44 publications
8
48
2
2
Order By: Relevance
“…Of note, the interactive effect hypothesis did not receive empirical support in the current study, because all relevant interaction terms were not statistically significant. Such absence of an interactive effect in the current study appears to contradict a prior study (Erdem et al 2016) reporting a statistically significant moderation effect between unemployment and neighborhood characteristics. However, the prior study (a) relied on cross-sectional data and focused on the role of concurrent neighborhood; (b) used data from a sample with a wide age range; and (c) did not specifically focus on unemployment experiences during young adulthood.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Of note, the interactive effect hypothesis did not receive empirical support in the current study, because all relevant interaction terms were not statistically significant. Such absence of an interactive effect in the current study appears to contradict a prior study (Erdem et al 2016) reporting a statistically significant moderation effect between unemployment and neighborhood characteristics. However, the prior study (a) relied on cross-sectional data and focused on the role of concurrent neighborhood; (b) used data from a sample with a wide age range; and (c) did not specifically focus on unemployment experiences during young adulthood.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, emerging evidence hints at an interactive effect. For example, according to a recent cross-sectional study from the Netherlands (Erdem et al 2016), the adverse mental health impact of unemployment was worse for people living in neighborhoods with lower social cohesion. No identified studies have evaluated these three feasible hypotheses in the context of the scarring effects of young adult unemployment and childhood neighborhood circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…This may be particularly salient for low-income and unpartnered mothers to reduce parenting in isolation (Stewart et al, 2009). Increasing social cohesion and reducing social isolation may result in improved mental health and perceived well-being outcomes (Cacioppo & Cacioppo, 2014;Erdem, Van Lenthe, Prins, Voorham, & Burdorf, 2016).…”
Section: Implications For Practice and Policymentioning
confidence: 99%
“…A population-based cohort study found that less socially cohesive neighborhoods were associated with a high prevalence of self-reported depressive symptoms [27]. Furthermore, Erdem et al (2016) discovered that living in cohesive neighborhoods alleviated psychological distress among economically deprived groups [49].…”
Section: Built Environment Social Interaction and Mental Healthmentioning
confidence: 99%